Mine 9 [videorecording (DVD)] - Serpico, Terry; Sizemore, Kevin, 1972-; Ashworth, Mark David (123 Go Films, 2020)
Two miles into the earth, nine Appalachian miners struggle to survive after a methane explosion leaves them with one hour of oxygen.